Efficiency of different methods of extraction and purification of cytokinins - Hoyerová, Klára; Gaudinová, Alena; Malbeck, Jirí; Dobrev, Petre I; Kocábek, Tomás; Solcová, Blanka; Trávnícková, Alena; Kamínek, Miroslav (Phytochemistry, 2006)
The increasing use of advanced methods, such as mass spectrometry, for the determination of cytokinins has raised special requirements for the extraction and purification of this class of plant hormones. Extraction of Arabidopsis thaliana plants with three different solvents, [80% (v/v) MeOH, Bieleski's MCF-7, and modified Bieleski's] provided similar yields of most analyzed cytokinins determined by high-performance liquid chromatography-tandem mass spectrometry (HPLC/MS/MS). However, the extraction with a modified Bieleski's solvent (MeOH-HCO2H-H2O [15:1:4, v/v/v]) gave the highest responses of deuterated cytokinins (used as test compounds) in plant extracts as compared to the responses of pure deuterated standards (relative internal standard response, RISR). Purification of cytokinins using Oasis MCX sorbent with reversed-phase and cation-exchange characteristics, in comparison to the DEAE Sephadex RP-C18 method, provided higher levels of zeatin riboside monophosphate and similar levels of cytokinin bases, ribosides and glucosides. Using this method the content of UV-absorbing contaminates was decreased by about 90% and the RISR values of all tested cytokinin standards but riboside monophosphates were increased about two-fold. The former method provided preparations more suitable for HPLC/MS/MS analysis with respect to simplicity and sample purity.
Keywords: Cytokinins; hmotnostní spektrometrie; Mass Spectrometry; vysokoúčinná kapalinová chromatografie; rozpouštědla; Molecular Structure; Arabidopsis; molekulární struktura; Chromatography, High Pressure Liquid; Efficiency; výkonnost; Solvents; cytokininy